The Microteaching Simulation Model as an Effective Approach to Improving the Teaching Skills of Islamic Religious Education Students at STAI Al-Azhary Cianjur - Muhamad Yusup Maulana; Siti Nurkasyifah; Mutia Selma Nafis; Euis Latipah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2025)
Microteaching is a highly essential approach in developing fundamental teaching competencies for prospective educators. This study aims to examine the effectiveness of the microteaching simulation model in enhancing the teaching skills of students in the Islamic Education (PAI) Study Program at STAI Al-Azhary Cianjur. Utilizing a descriptive qualitative method, data were collected through classroom observations, interviews with students and lecturers, and documentation. The findings indicate that the implementation of microteaching simulations significantly supports the improvement of students' skills, particularly in lesson openings, classroom management, providing feedback or reinforcement, and systematically closing lessons. Additionally, students demonstrated increased self-confidence and enhanced ability to reflect on their teaching practices. Based on these results, this model is recommended for consistent implementation in teacher education programs, especially in microteaching courses.